Sustainable Utilisation of Beach Sand as Fine Aggregate Replacement and Its Effect on Concrete Strength with Admixtures Reinforcement - Hamdani, Hafiz; Zarkasi, Ahmad; Fitrayudha, Adriyan; Akhsae, I Gede Anaga; Pratama, Khendy Marsha Duta (Journal La Multiapp, 2025)
This research was conducted to review the feasibility of beach sand from the Batu Bolong village of West Lombok Region as an alternative fine aggregate in concrete manufacturing. The background of this research is based on the decreasing supply of sand from rivers and mountains. The main objective of this research was to evaluate the compressive strength of concrete using beach sand, both with and without a washing process, and assess whether this material could be applied in structural construction. In addition to technical aspects, the local community's habit of utilizing beach sand is also part of the consideration in this study. The result oh the tests showed that the compressive strength of normal concrete without admixtures at 3, 7, and 28 days of age were 16.42 MPa, 19.21 MPa, and 23.39 MPa, respectively. The addition of the "BETON MIX" admixture increased the strength to 20.78 MPa, 23.38 MPa, and 26.44 MPa. Meanwhile, concrete using washed beach sand showed compressive strengths of 22.67 MPa, 23.61 MPa, and 25.16 MPa. The concrete with unwashed beach sand produced strengths of 21.72 MPa, 22.40 MPa, and 23.08 MPa. The results of this study indicate that sand from Batu Bolong beach has the potential to be a substitute for fine aggregate in concrete. However, its use must still consider ecological impacts so as not to disturb the balance of the coastal environment.